Complete genome sequence of Syntrophobotulus glycolicus type strain (FlGlyRT) - Han, C.; Mwirichia, Romano K.; Chertkov, O.; Lapidus, A.; Nolan, M.; Brambilla, Evelyne-Marie; et al. (My University, 2011)
Syntrophobotulus glycolicus Friedrich et al. 1996 is currently the only member of the genus Syntrophobotulus within the family Peptococcaceae. The species is of interest because of its isolated phylogenetic location in the genome-sequenced fraction of tree of life. When grown in pure culture with glyoxylate as carbon source the organism utilizes glyoxylate through fermentative oxidation, whereas, when grown in syntrophic co-culture with homoacetogenic or methanogenic bacteria, it is able to oxidize glycolate to carbon dioxide and hydrogen. No other organic or inorganic carbon source is utilized by S. glycolicus. The subdivision of the family Peptococcaceae into genera does not reflect the natural relationships, particularly re-garding the genera most closely related to Syntrophobotulus. Both Desulfotomaculum and Pelotomaculum are paraphyletic assemblages, and the taxonomic classification is in signifi-cant conflict with the 16S rRNA data. S. glycolicus is already the ninth member of the family Peptococcaceae with a completely sequenced and publicly available genome. The 3,406,739 bp long genome with its 3,370 protein-coding and 69 RNA genes is a part of the Genomic Encyclopedia of Bacteria and Archaea project.
DOI:10.4056/sigs.2004684
Keywords: glycolate-oxidizing; Gram-negative with Gram-positive cell wall structure; strictly anaerobic; chemotrophic; mesophilic; non-motile; rod-shaped; spore-forming; Peptococca-ceae; Clostridiales; GEBA